Social Protection and Cash Transfers in Mozambique: between international consensus and local agency - Oliveira, Maria Clara; Cravo, Teresa Almeida (Cadernos de Estudos Africanos, 2021)
This article examines the rise of cash transfer programs and their embrace, since the 1990s, as a central element in global public policy on economic and social development and poverty reduction. Focusing on the example of Mozambique, an early adopter of such programs, it analyses the relationship between international organizations, development aid agencies, national government and local agents in the field, in the design and delivery of social protection policy. While external actors have been important in shaping Mozambican public policy, this study reveals the relevant role played by the country’s domestic actors in agenda-setting, conception and implementation of a cash transfer program as early as 1990, and its evolution over the subsequent three decades. In this interplay between international and local levels of decision- and policy-making, the article looks into the barriers to the program’s reach, pace and limited impact.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; social protection / proteção social

The Political Economy of Social Protection in Mozambique - Buur, Lars; Salimo, Padil (SSRN Electronic Journal, 2018)
In the view of international donors, multilateral organisations and government officials, social protection in Mozambique benefits from strong government commitment to it. Their argument is that, in contrast to many African countries, the government has demonstrated a level of commitment and support to social protection that is quite unprecedented. This view relies on the fact that more than 90 per cent of the budget allocated to the implementation of social protection programmes comes from the state budget and that, even within the complex context of the financial crisis that has devastated the economy since 2013, social protection has continued to receive special attention from the government in its budget allocations. Based on a political economy analysis, this paper challenges the common narrative of social protection in Mozambique, by arguing that social protection has been used as a means to mobilise resources from international agencies, in order to ensure the political survival of the Frelimo government. The paper argues that government support of social protection emerged as a reaction to the poor performance of poverty-reduction initiatives, becoming also a mechanism to overcome social protests after the 2008 and 2010 riots in Mozambique, which threatened to jeopardise the stability of the regime and its reproduction of power.
Keywords: *indexed; *tagged; Ethnographic Studies; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Social Protection PEA; development partners / parceiros de cooperação; social protection / proteção social